PESAN – PESAN MORAL ORANG TUA ETNIS TIONGHOA DALAM MENDIDIK ANAKNYA - Zevanya Sara Sulistio (KAREBA : Jurnal Ilmu Komunikasi, 2016)
This study aimed (1) to determine the moral messages of Chinese parents in educating their children; (2) to determine the openness in interpersonal communication between parents and children of delivering moral messages; (3) to determine the obstacles of delivering moral messages between parents and children.This study is located in Pecinan town, District Wajo, Makassar city. The informants in this study were the leaders of chinese society and chinese families determined by purposive sampling based on certain criterias. The type of this study is descriptive qualitative which describes the problems examined by the results of indepth interview of informants.Techniques of data collection done in two ways, through primary and secondary data. Primary data was collected through in-depth interviews and secondary data collected through literature. All data collected will be analyzed by descriptive qualitative.The results showed that moral message of chinese parents came from confucianism namely Bādà (八大) and Dìzĭ Guī (弟子規), which devotion to parents and ancestors become the most important and fundamental moral messages in chinese families at Makassar city. In the process of delivering a moral message between parents and children happen openly. Parents provide space for children to dialogue if there is a moral message that is not appropriate or not understood by children. Obstacle in the process of delivering a moral message is perceptual distorsion between parents and children. Tujuan studi ini adalah : (1) Untuk mengetahui pesan – pesan moral yang di berikan orang tua Etnis Tionghoa dalam mendidik anaknya; (2) Untuk mengetahui keterbukaan yang berlangsung dalam proses komunikasi antarpribadi antara orang tua dan anak dalam proses penyampaian pesan-pesan moral; (3) Untuk mengetahui hambatan – hambatan yang terjadi dalam proses penyampaian pesan-pesan moral oleh orang tua kepada anak.Studi ini dilaksanakan di Pecinan Town, Kecamatan Wajo, Kota Makassar. Adapun informan studi ini adalah Tokoh Masyarakat Etnis Tionghoa dan keluarga Etnis Tionghoa yang ditentukan dengan teknik purposive sampling berdasarkan kriteria tertentu. Tipe studi yang digunakan adalah deskriptif kualitatif, yang menjelaskan tentang masalah yang diteliti berdasarkan hasil wawancara mendalam terhadap informan.Teknik pengumpulan data dilakukan dengan dua cara yakni melalui data primer dan sekunder. Keseluruhan data yang berhasil dikumpulkan kemudian dianalisis secara deskriptif kualitatif.Hasil studi menunjukkan pesan-pesan moral Etnis Tionghoa berasal dari ajaran konfisius yaitu Bādà (八大) dan Dìzĭ Guī (弟子規), dimana bakti kepada orang tua dan leluhur yang menjadi pesan terpenting dan mendasar dalam keluarga etnis Tionghoa di Kota Makassar. Dalam proses penyampaian pesan moral dari orang tua kepada anak, berlangsung dengan terbuka. Orang tua memberi ruang untuk berdialog jika ada pesan moral yang tidak sesuai atau tidak dimengerti oleh anak. Faktor penghambat dalam proses penyampaian pesan moral adalah beda pendapat atau perceptual distorsion antara orang tua dan anak.